Crystal structure of a natural light-gated anion channelrhodopsin - Hai Li; Chia-Ying Huang; Elena G Govorunova; Christopher T Schafer; Oleg A Sineshchekov; Meitian Wang; Lei Zheng; John L Spudich (eLife, 2019)
The anion channelrhodopsin GtACR1 from the alga Guillardia theta is a potent neuron-inhibiting optogenetics tool. Presented here, its X-ray structure at 2.9 Å reveals a tunnel traversing the protein from its extracellular surface to a large cytoplasmic cavity. The tunnel is lined primarily by small polar and aliphatic residues essential for anion conductance. A disulfide-immobilized extracellular cap facilitates channel closing and the ion path is blocked mid-membrane by its photoactive retinylidene chromophore and further by a cytoplasmic side constriction. The structure also reveals a novel photoactive site configuration that maintains the retinylidene Schiff base protonated when the channel is open. These findings suggest a new channelrhodopsin mechanism, in which the Schiff base not only controls gating, but also serves as a direct mediator for anion flux.